Electrical energy audit and potential energy saving measures for commercial building - Darus, Nabihah (2022)
Electrical energy audit is an examination of the energy consumption of the equipment or system to ensure that energy is being used efficiently. It acts as a systematic assessment of the baseline energy consumption efficiency within a facility, followed by identification of energy efficiency improvement opportunities and cost-saving measures that can be implemented to ensure the efficient energy consumption in any building. The electrical energy audit has gained attention across all energy sectors such as residential, commercial, and industrial since energy consumption gives immediate impact on costs considerable and impact on environmental sustainability. Due to problem related to energy management and energy efficiency such as regulation imposed, cost and environmental factor, the electrical energy audit currently has been found as one of the methods that can ensure the sustainability of energy in the future since energy audit activities are able to determine suitable steps and precaution to be undertaken to use energy efficiently. This study measured the energy consumption on commercial building which is an office of building. The main purpose of this study is to evaluate the electrical energy consumption focused on commercial building that will contribute to the framework of potential energy saving measure for future implementation. Therefore, three objectives were focused on which are to evaluate the existing energy management practice of a commercial building, identify historical and present energy usage pattern of the building and proposed Energy Conservation Measures (ECMs) by evaluating the cost analysis for each ECMs proposed. Walk through or preliminary energy audit is performed to obtain data related. The data included the building details and end-use load cycles. Linear regression and statistical analyses were used to analyse all the data obtained from the preliminary audit and on-site measurement. Besides, significant variables were used to determine the actual energy consumption implementation cost and savings. By referring to Measurement and Verification Method (Option D – Calibrated Simulation), the General Algebraic Modelling System (GAMS) software is used to analyse the optimum energy consumed by the loads considered. Then, the framework of potential energy saving measure was proposed for future energy consumption used that covered on no/low-cost measures, medium cost measures and high-cost measures. The proposed energy saving measure show significant reduction in energy consumption and operating cost also show reduction that led to savings. The low-cost measure show reduction between 10% to 11% of energy saving. The medium-cost implementation shows the best performance in terms of payback period which is less than 1 year depending on ESM proposed. High-cost measure shows the best performance in energy consumption reduction around 90% of total usage. This proposed framework could enable energy consumption been monitor and propose saving measure can be implemented to achieve efficient energy use.